2017
DOI: 10.3897/zoologia.34.e14881
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic diversity in Callithrix hybrids in an anthropogenic area in southeastern Brazil (Primates: Cebidae: Callitrichinae)

Abstract: ABSTRACT. Two species of Callithrix, C. jacchus (Linnaeus, 1758) and C. penicillata (É. Geoffroy, 1812), are considered invasive in Rio de Janeiro. This study determined the genetic and morphological diversity and verified the species involved in the hybridization of 10 individuals from the municipalities of Silva Jardim (N = 9) and Rio das Ostras (N = 1). We compared the The results corroborate that C. jacchus and C. penicillata participate in the hybridization process. There was no geographic structure betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In this research we observed that the auricular tufts of the free range marmosets do not match to the description of any species of the genus but are dark brown, dark gray or light gray with mixed strands, arranged anterior or around the ear and broken in some parts, forming a mosaic, suggesting the animals are hybrids and also they are probably outcomes of more than one generation of hybrids. This result is similar, in parts, with the research done by Cezar (2017) in natural and anthropogenic areas but different from the phenotypes found in a natural hybridization area, where the hybrids maintained tufts similar to their parental, being totally dark or totally light (Valdivino et al 2003).…”
Section: Morphologic Datasupporting
confidence: 69%
“…In this research we observed that the auricular tufts of the free range marmosets do not match to the description of any species of the genus but are dark brown, dark gray or light gray with mixed strands, arranged anterior or around the ear and broken in some parts, forming a mosaic, suggesting the animals are hybrids and also they are probably outcomes of more than one generation of hybrids. This result is similar, in parts, with the research done by Cezar (2017) in natural and anthropogenic areas but different from the phenotypes found in a natural hybridization area, where the hybrids maintained tufts similar to their parental, being totally dark or totally light (Valdivino et al 2003).…”
Section: Morphologic Datasupporting
confidence: 69%
“…Although all the marmoset (non-human primate) samples were negative, is important to monitor these animals for Bartonella infection, given that some Callithrix species, such as C. jacchus and C. penicillata , are invasive in Rio de Janeiro, where they have been introduced from other regions of Brazil through the illegal animal trade ( Cezar et al, 2017 ). This finding, and the lack of records of Bartonella infection in other Brazilian studies of non-human primates, may be related to low bacteremia in these animals, which would hamper molecular detection ( Bonato et al, 2015 ; Breitschwerdt, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these patterns, the question arises if there is more selective pressure in C. jacchus x C. penicillata hybrids to minimize developmental disturbance of cranial morphology than post-cranial morphology. Retaining the exudivory specialization of their parental species likely enables C. jacchus x C. penicillata hybrids to use plant exudates as a fallback food, and contribute to these hybrids being the most common hybrid type present in anthropogenic Callithrix hybrid zones in the southeastern Brazilian Atlantic Forest [28, 27, 73, 36]. These factors may affect the ability of such hybrids to successfully exploit plant exudates as fallback foods relative to C. jacchus and C. penicillata hybrids.…”
Section: Discussionmentioning
confidence: 99%